The effect of wattpad application towards students' reading comprehension in report text (An Experimental Study at the Tenth Grade Students of SMAN 2 Malingping Lebak Banten in the Year Academic 2023/ 2024) - Padillah, Anisa; Sudirnab, Ade; Novari, Ari Fajria (CV. Kurnia Grup, 2024)
The aim of this research is the significant effect of the Wattpad application significantly improves the reading comprehension abilities of class X students at SMAN 2 Malingping. Using a pre-test and post-test group design, the methodology used is quasi-experimental, and the research methodology is quantitative. The population of this research was 94 students, and the sample was 60 students. In analyzing the data, researcher used achievement tests with SPSS 25 statistical computing to analyze hypothesis tests. Researcher obtained tcount results (0.285) and two-sided significance = 0.465 < α 0.05. From this data it can be interpreted that there is a significant difference between the two groups in obtaining scores, because the result is a significant value grether than 0.05, which means Ha is accepted. Therefore, the researcher concluded that the application of Wattpad had a good role in students' reading comprehension skills of report texts. Apart from that, the Wattpad application, apart from being effective in learning to read, can also be used as a medium for reading online books because the Wattpad application has free space for communication between teachers and students as well as between students and other teachers use the comments column provided.